Minimization of Power Loss as a Design Criterion for the Optimal Synthesis of Loader Drive Mechanisms - Jovan Pavlović; Vesna Jovanović; Dragan Marinković; Dragoslav Janošević; Žarko Ćojbašić (Applied Sciences, 2025)
As energy efficiency becomes a significant performance indicator in mobile machines, power losses are recognized as an important criterion in the design and optimization of these systems. This paper analyses the loads and power loss due to friction in the revolute joints of the manipulator drive mechanisms during all phases of the loader manipulation task, based on dynamic simulations of the loader model with different variants of Z-kinematics manipulator drive mechanisms, using the MSC ADAMS 2020 software. The analysis is based on a general dynamic mathematical model of the loader, which enables the assessment of the influence of the parameters of the manipulator mechanisms on the functional, structural, and tribological characteristics of the revolute joints within the manipulator’s kinematic chain. Based on the analysis results, a minimum power loss criterion was defined as part of a multi-criteria optimal synthesis procedure for the manipulator drive mechanisms, with the objective of maximizing energy efficiency by minimizing power loss caused by friction in the revolute joints of the manipulator drive mechanisms.